2005
DOI: 10.1007/s11325-005-0017-y
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea syndrome: effect of respiratory events and arousal on pulse wave amplitude measured by photoplethysmography in NREM sleep

Abstract: Obstructive sleep apnea syndrome: effect of respiratory events and arousal on pulse wave amplitude measured by photoplethysmography in NREM sleep Abstract The objective of the study is to evaluate changes in finger pulse wave amplitude (PWA), as measured by photoplethysmography, and heart rate (HR), related to obstructive respiratory events and associated arousals during sleep. We analyzed 1,431 respiratory events in NREM sleep from 12 patients according to (1) the type of event (apnea, hypopnea, upper airway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 28 publications
3
40
2
2
Order By: Relevance
“…Moreover, these last authors recently showed better correlation between pulse wave amplitude changes and acoustical-induced arousals undetected by EEG than with other autonomic markers. In patients with SAS, we recently confirmed that RE and A induce more changes in PWA than changes in HR as measured by photoplethysmography [18]. We also found more changes in PWA than HR after RE without cortical arousal.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Moreover, these last authors recently showed better correlation between pulse wave amplitude changes and acoustical-induced arousals undetected by EEG than with other autonomic markers. In patients with SAS, we recently confirmed that RE and A induce more changes in PWA than changes in HR as measured by photoplethysmography [18]. We also found more changes in PWA than HR after RE without cortical arousal.…”
Section: Introductionsupporting
confidence: 67%
“…Subtle subcortical or autonomic arousals seem also to play a role in SAS. RE not only induce arousals but also changes in autonomic markers such as heart rate (HR) [8,9], blood pressure [10], peripheral arterial tonometry (PAT) [11][12][13], pulse transit time (PTT) [14][15][16], and photoplethysmography [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Since CAP probably reflects subcortical as well as cortical activation, finding this result suggests that the frequency of both cortical and subcortical arousals together might be better related to sleep quality than either alone. Although primary attention in doing this kind of analysis has focused mostly on EEG signal analysis, the difficulty in doing this may outweigh the simplicity of our approach which focuses on HR, rather than on harder to measure autonomic measures such as pulse wave transit time or pulse amplitude (Pitson and Stradling, 1998;Haba-Rubio et al, 2005). During REM sleep, bouts of tachycardia-bradycardia occur without any detectable change in the EEG power spectrum (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[18], and the PLMS index (PLMSI) was calculated. As autonomic arousals were considered, the pulse-wave amplitude (PWA) drops (of at least 30% of baseline PWA) obtained from finger photoplethysmography, reflecting peripheral vasoconstriction [19,20]. The number and index per hour of sleep of autonomic arousals were calculated.…”
Section: Polysomnographymentioning
confidence: 99%